"It Made a Difference to Me": A Comparative Case Study of Community Pharmacists' Care Planning Services in Primary Health Care - Theresa J. Schindel; Rene R. Breault; Christine A. Hughes (MDPI AG, 2019)
In some jurisdictions, governments and the public look to community pharmacies to provide expanded primary health care services, including care plans with follow-up. Care planning services, covered by the Compensation Plan in Alberta, Canada, require pharmacists to assess an eligible patient’s health history, medication history, and drug-related problems to establish goals of treatment, interventions, and monitoring plan. Follow-up assessments are also covered by the Compensation Plan. A comparative case study method facilitated an in-depth investigation of care planning services provided by four community pharmacy sites. Data from 77 interviews, 61 site-specific documents, and 94 h of observation collected over 20 months were analyzed using an iterative constant comparative approach. Using a sociomaterial theoretical framework, the perceived value of care planning services was examined through an investigation of the relationships and interactions between people and information. Patients perceived the value of care planning as related to waiting time to access care and co-creating individualized plans. Physicians and other health care professionals valued collaboration, information sharing, and different perspectives on patient care. Pharmacists valued collaboration with patients and other health care professionals, which renewed their sense of responsibility, increased satisfaction, and gave meaning to their role.